Dziewictwo rozumiane jako ustawiczna walka dla Pana: fundamenty biblijne w liście 22 św. Hieronima do Eustochium - Turek, Waldemar Jan (Vox Patrum, 2020)
St. Jerome deals with many themes in his Letter 22 to Eustochium, but the author focuses on virginity interpreted as a constant struggle for the Lord and he analyses the Biblical foundations of this exposition. He first tries to clarify St. Jerome’s purpose as he wrote this letter, that is, the articulation, in the light of the Bible, on the one hand of the reason and beauty of life in virginity, and on the other hand the difficulties and renunciations that have to be constantly undertaken so as to persevere in this state. He then discusses the pertinent Biblical references, primarily from the New Testament and in particular from the Gospels and the letters of the apostle St. Paul. He analyses their use, the chosen expressions and terms (sometimes taken from the vocabulary of sportsmen and soldiers) and their literary and doctrinal context. He then lists concrete elements of the spiritual struggle undertaken by the virgin for Christ (prayer, meditating of the Sacred Scriptures, silence, fasting, remaining at home, various mortifications pertaining to the body and spirit), as the Lord has personally given us proofs of supreme love, poverty and perseverance in the withstanding of sufferings. Finally, in the context of the continuously actual debate about virginity and marriage, he questions the value of the discussed Letter 22 of St. Jerome for this theme within a Biblical, Christological, ecclesiological and eschatological perspective. Keywords: virgin, virginity, chastity, marriage, struggle, body, soul, unmarried state, concupiscence, poverty, patience, suffering, renunciation, mortification, fasting, continence.